Running-related injury: How long does it take? Feasibility, preliminary evaluation, and German translation of the University of Wisconsin running and recovery index. (November 2021) - Hoenig, Tim; Nelson, Evan O.; Troy, Karen L.; Wolfarth, Bernd; Heiderscheit, Bryan C.; Hollander, Karsten
Abstract: Objective: The University of Wisconsin Running Injury and Recovery Index (UWRI) was developed as an evaluative patient-reported outcome measure of perceived running ability and recovery after running-related injuries. To date, the questionnaire was not translated into German language and studies on its clinical feasibility and validity are sparse. Design: Prospective cohort study. Setting: Outpatient sports medicine clinic. Participants: The UWRI questionnaire was translated to German language using a state-of-the art back-translation method including three translators and two back-translators. Clinical feasibility and validation were assessed in 14 injured runners. Main outcome measures: UWRI total score, running volume. Results: The translation process was completed without major discrepancies. Feasibility and preliminary evaluation were demonstrated in a cohort of 14 injured runners. The UWRI total score significantly improved throughout 12 weeks of recovering from running-related injuries (p < 0.001). Relative running volume significantly correlated with UWRI score (p < 0.001). Conclusion: The University of Wisconsin Running Injury and Recovery Index was successfully translated into the German language. Its usage may hold promise for better rehabilitation surveillance following running-related injuries. Highlights: The UWRI provides information on the recovery from a running-related injury. This patient-reported outcome measure can be successfully translated and culturally adapted. This study indicates its feasibility and validity in a clinical setting. Usage of the UWRI may hold promise for better rehabilitation surveillance.